Питания приватного права в дослідженнях вчених-юристів Київського комерційного інституту - Міхневич, Л.В. (Часопис Київського університету права, 2009)
Статья посвящена малоизученному вопросу - исследование опыта развития юридической науки в Киевском коммерческом институте (1906-1920 гг.). Проанализированы основные труды ученых-юристов института в области частного права. Освещены наиболее характерные и интересные идеи ученых. Обоснован вывод о значительном влиянии научных достижений юристов института на развитие отечественной юридической науки. The article is devoted to the question that is not studied very well - the research of the experience of the law science development in the Kyiv Commercial institute (1906 -1920). The main works of the lawyers-scientists representing the institute in the sphere of the private law have been analyzed. The most interesting and typical ideas of the scientists have been outlined and highlighted. The findings about the considerable impact of the scientific achievements of the institutes lawyers towards the contemporary Ukrainian law science has been put on a substantial grounds.